INTERNALISASI NILAI-NILAI SPIRITUAL RELIGIUS: Studi Kasus di Ribat Tazkiyat al-Nafs Tarekat Qadiriyah wa Naqsyabandiyah Bengkulu Selatan - Ramadhani, Rizki; Ibrahim, Duski; Munir, Munir (Conciencia, 2019)
In Indonesia in general the community began to lead to a materialistic and hedonic attitude. They make material a measure of success and happiness. As a result, people often lose control. The more visible humans justify any means to achieve goals. In fact, true happiness and peace of mind cannot be obtained from material, position, long life and freedom. For those who do not find happiness and peace of mind with their glamor, the world seeks tranquility or happiness in its soul by reciting and following the tarekat. The practicing people believe, feel, and declare that through the practice of the teachings and practices of the tarekat this inner peace and essential happiness can be achieved. Of course, this was achieved not apart from the role of murshid who consistently guided and nurtured the spiritual practitioners through their practices and teachings. This means that spiritual education in the form of internalizing religious spiritual values ​​instilled by the murshid to the practitioners of the tarekat Qa> diriyah wa Naqsyabandiyah in Riba> t Taz \ kiyat al-Nafs South Bengkulu has a tremendous impact on changes in both psychological and mental and spiritually the practicers who in the end are able to change the behavior of the practicing person into a commendable person.